PENGARUH KOMPETENSI KEWIRAUSAHAAN, ORIENTASI KEWIRAUSAHAAN, DIGITAL MARKETING TERHADAP KINERJA BISNIS JASA LAUNDRY SEPATU DI KABUPATEN PONOROGO - Pramudya, Dimas Alfikri; Farida, Umi; Santoso, Adi (ANALISIS, 2023)
This study aims to determine whether Entrepreneurial Competence, Entrepreneurial Orientation, Digital Marketing influence the Performance of the Shoe Laundry Service Business in Ponorogo Regency. This research is quantitative. The size of the population in this study is unlimited shoe laundry business people, so the sample determination uses the Hair formula, so that a sample of 65 respondents is obtained through the snowball sampling technique used in the sampling technique. Methods of data collection using observation and questionnaires. The data analysis used is multiple linear analysis. The research results prove the multiple linear analysis Y = 4.771 + 0.380X1 + 0.272X2 + 0.314X3. The R2 value of the coefficient of determination of the variables X1, X2, X3 is 0.256 which means entrepreneurial competence, entrepreneurial orientation and digital marketing) are able to contribute to business performance by 25.6%, remaining 74.4%, namely contributions from other factors outside of this research. Simultaneous test (f) proves that the calculated F value is greater than F table (6.997 > 2.76) the significance value is less than (0.000 <0.05) it is concluded that entrepreneurial competence, entrepreneurial orientation, digital marketing together have a significant positive effect on the performance of the shoe laundry service business in Ponorogo district. The conclusion of the partial test (t) proves 1). Entrepreneurial competency variable has a significant and positive effect on business performance. 2). Entrepreneurial orientation variable has a significant positive effect on business performance. 3). Digital marketing variables have a significant positive effect on business performance.